Re-participation intention in individuals playing tennis for recreational purposes: investigation of differences based on low and high involvement - Omur Fatih Karakullukcu; Cihan Ayhan; Tugcenur Kalkan; Bilal Okudan; Laurentiu-Gabriel Talaghir; Teodora Mihaela Iconomescu (Frontiers in Psychology)
PurposeThis study examined how the level of involvement influences the re-participation intentions of recreational tennis players.MethodTo measure the participants’ leisure involvement levels; the leisure involvement scale, developed by Kyle et al. (2007) and adapted to the Turkish language by Gürbüz et al. (2018) was used. The behavioral intentions scale developed by Zeithaml et al. (1996) was used to measure participants’ re-participation intentions. The research group consists of a total of 327 volunteer individuals, 172 males (52.6%) and 155 females (47.4%), selected by convenience sampling method among individuals who play tennis for recreational purposes. The normality test of the data obtained was tested by checking the skewness-kurtosis values and it was determined that the data showed normal distribution. In this context, in addition to descriptive statistics, Hierarchical-Non-Hierarchical Clustering Analysis, and Univariate analyses were used in the analysis of the data.ResultsAccording to the research findings, it was determined that there was a statistically significant difference in the re-participation intentions of the participants who played tennis for recreational purposes according to their involvement levels.ConclusionIt was observed that participants with high involvement levels had higher re-participation intentions than those with low involvement.